The Effect of using Ceftiofur drug on estrogen (E2) and progesterone (P4) concentrations during post parturition period in dairy cattle with Bacterial Endometritis - Mustafa Wasman, Hunar; Anwar Hassan, Karwan; Jalel Ibrahem, Emad (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Postpartum infertility is caused by a range of different conditions. In female cattle, uterine infections are one of the most common causes. As a result, the affections of uterine infections will reduce in dairy herds fertility. In this investigation, samples were taken by using double guard swaps from the uterus of cattle that had passed nine to ten days after calving. They were divided into two groups depending on the number of colonies which were over 12 colonies. Twenty cows in the first group were treated with Ceftiofur hydrochloride (injection) subcutaneously, and the treatment was carried out twelve days after the calving process, and it took four days consecutively. The second group has remained as the control group as long as it represented 18 untreated cattle. After calving, the procedure of collecting samples began, which took place on days 5, 12, 19, and 26. The results indicated that the level of estrogen in the Ceftiofur treated group had reached its peak (maximum level) on the twelfth day after delivery. On day 12, the level of progesterone in the ceftiofur-treated group was greater than the control group significantly. Furthermore, in both of the groups, the level of progesterone had reached its maximum level on day 26, however it was higher in the ceftiofur-treated group than in the control group, but no significant distinguish was observed (<0.05). Conclusively, according to the results, it was observed that after using ceftiofur, the amount of estrogen production, especially in cow with multiple births, was significantly higher than the control group (<0.05), which reveals the effect of the drug on this group. Also, the level of progesterone in the Ceftiofur treated group was significantly higher, especially in cattle with several calvs. As a result, it is possible to deduce that ceftiofur can influence estrogen and progesterone secretion by reducing the number of uterine bacteria.